Band-gap shrinkage in n-type-doped CdO probed by photoemission spectroscopy - Dou, Y; Fishlock, T; Egdell, R; Law, D; Beamson, G (1997)
The influence of n-type doping CdO with In or Y has been investigated by high-resolution ultraviolet and x-ray photoemission spectroscopy. It is found that core levels and valence band features suffer a shift to high binding energy due to doping. However this shift is less than the change in the width of the occupied conduction band. This provides a direct measurement of band gap shrinkage as a result of doping in an oxide semiconductor.